(untitled) (Modern education and development, 2025)
Color is the most important part of all visual information. It is the color of the clothes of the person you meet, the color of his face, hair, etc. that is remembered first of all. Out of the few available linguistic studies, one can rely on introspection when drawing conclusions: examining the behavior of color terms in contexts through language analysis, the meanings of color definitions are revealed. Color is the subject of many scientific studies.One of the issues related to color naming is the question of what principle should be used to combine words denoting color into groups.